Calderón : The Secular Plays - Ter Horst, Robert, 1929- (Book collections on Project MUSE., 1982)
Although Pedro Calderón de la Barca was one of the greatest and most prolific playwrights of Spain's Golden Age, most of his nonallegorical comedias -- 118 in all -- have remained unknown. Robert ter Horst presents here the first full-length study of these works, a sustained, meditative analysis dealing with more than 80 plays, conveying a sense of the whole of Calderón's secular theater. To approach so vast a body of literature, Mr. ter Horst examines the meaning and function in Calderón of three broad subjects -- myth, honor, and history -- the warp threads across which the playwright weaves.